Estimating the impact of immigration on housing prices and housing affordability in New Zealand - Chanpiwat, Nipat (Auckland University of Technology, 2013)
This research examines the response of New Zealand housing markets to immigration shocks. The effects of migrants in general have been widely debated in New Zealand, and have been the focus of many studies around the world. This research focuses solely on the impact of migration on the issue of housing, the largest component of peoples’ wealth. Drawing on housing, migration and census data between the years 1996 to 2011, the regression analysis in this study reveals that there was a positive correlation between external migration shocks and house prices. A 1% migration shock increased house prices by approximately 7.5% on a national scale. Furthermore, it is found that smaller housing markets are less able to ‘cope’ with housing pressure exerted by migrants, compared to bigger cities where migrants tend to cluster. This research suggests that the possible existence of supply constraints in the New Zealand housing market, whereby the market is unable to adjust to a sudden inflow of overseas migrants.
Keywords: Immigration; House prices